Green recovery optimization of phenolic compounds from “Spinoso sardo” globe artichoke by-products using response surface methodology - Cannas, Michela; Conte, Paola; Piga, Antonio; Del Caro, Alessandra (Frontiers in Sustainable Food Systems, 2023)
The reuse and valorization of agri-food by-products is a pivotal activity in the pursuit of a circular model that can improve sustainability and efficiency of agri-food production. During artichoke processing, 60-80% of the biomass produced by the plant consists of inedible fractions, which nevertheless represent a natural source of high value-added compounds, such as phenolics. In this study, response surface methodology was applied to investigate and optimize the amount of ethanol and the reduction of extraction time to achieve the maximum yield of polyphenols and flavonoids from artichoke stems, leaves, and bracts, by using two extraction methods, namely maceration and ultrasound-assisted extraction. Overall, phenolic compounds were most concentrated in extracts obtained from the stems, followed by those derived from the bracts and leaves, with the percentage of ethanol being the most influential factor. After applying the optimization criteria, the best factor setting to achieve maximum extraction yields and strong antioxidant capacities was: 53% ethanol for stems, 45% for leaves, and 50% for bracts and 60 min for all by-products in the case of maceration; 10 min for stems and leaves with 42 and 20% of ethanol, respectively, and 41 min and 64% ethanol for bracts in the case of ultrasound-assisted extraction. Comparison between the two techniques evidenced that maceration was significantly more efficient, but similar recoveries were obtained with ultrasound-assisted extraction in shorter extraction time and lower ethanol consumption. Therefore, using this unconventional method to convert Spinoso Sardo artichoke by-products into bioactive ingredients with interesting industrial applications could be a viable strategy to reduce food losses and mitigate related environmental impacts.